(untitled) (Journal of Environmental Science and Natural Resources, 2016)
This study focuses on the influence of conservation tillage on carbon sequestration mechanism related to aggregation. Conservation tillage reduces the process of rapid microaggregates formation and mineralization into the microaggregates essentially a positive influence of soil aggregation on the build up of organic matter. The Carbon mineralization is four or five times higher in crushed free micro aggregates than in crushed macroaggregates. As a result conservation agriculture ensures higher carbon sequestration in soil rather than the conventional agriculture. However, the carbon sequestration for different tillage has significant variations at 1-10 cm depth but the variations in non significant for higher depth. The carbon sink potential for conservation agriculture is much higher but it differs due to climate, soil type, nutrient use soil cover and the methodology used. J. Environ. Sci. & Natural Resources, 9(1): 23-27 2016